Pentingnya Penegakan Hukum dan Hak Asasi Manusia Terhadap Narapidana di Penjara (Studi Kasus Lapas Narkoba Kelas IIa Yogyakarta 2022) - Zevanya, Keisha; Hania, Sally; Alysha, Nabila; Prabandari, Ditia; Arista, Naurah; Syajidah, Hanna Alicia; Manohara, Safa; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
This study reviews the urgency of law enforcement and protection of human rights (HAM) for prisoners in correctional institutions, with a focus on the Class IIA Yogyakarta Narcotics Prison. Based on the 2022 Komnas HAM report, human rights violations were found in the form of torture and inhumane treatment of inmates. This study uses a normative legal approach by relying on secondary data from legal regulations, scientific literature, and investigative reports. The findings show that the correctional system still faces various serious problems related to human rights protection, such as a weak supervision system and the practice of abuse of power. This study recommends the implementation of the Optional Protocol to the Convention Against Torture (OPCAT), correctional policy reform, and officer training based on human rights values. This study is primarily intended to contribute to the development of a correctional institution that is safe, humane, and adheres to the principles of justice.